Inhibitors on fuels corrosivity, containing oxygenates - Шевченко, О.Б.; Гулямов, Ю.М. (Proceedings of National Aviation University (archive), 2006)
Results of inhibitor selection for fuels containing spirits aresubmitted. The effective composition from 3 components of combined action is developed.